2022
DOI: 10.7717/peerj.13131
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of cadmium stress in rice by inoculation of Bacillus cereus

Abstract: Heavy metal resistant bacteria are of great importance because they play a crucial role in bioremediation. In the present study, 11 bacterial strains isolated from industrial waste were screened under different concentrations of cadmium (Cd) (100 µM and 200 µM). Among 11 strains, the Cd tolerant Bacillus cereus (S6D1–105) strain was selected for in vitro and in vivo studies. B. cereus was able to solubilize potassium, and phosphate as well as produce protease and siderophores during plate essays. Moreover, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Inoculation with Pseudomonas strains reduced Pb-induced toxicity and improved the growth, yield and physiology of sunflower plants, as observed in the present study [28]. Our results are supported by previous studies of metalstressed rice plants in which inoculation with Bacillus cereus and Bacillus subtilis remarkably increased shoot and root growth [45,46], which could be attributed to the phytohormone production and phosphate solubilization potential of inoculated rhizobacterial strains that help rice plants to acclimatize against the stressful environments [47]. Thus, it can be concluded that improvements in plant growth by Pb-resistant rhizobacterial strains in Pbcontamination soils could be due to phosphate solubilization, phytohormone production, siderophore production, and induced systemic resistance in metal-stressed plants [13,14,39].…”
Section: Discussionsupporting
confidence: 91%
“…Inoculation with Pseudomonas strains reduced Pb-induced toxicity and improved the growth, yield and physiology of sunflower plants, as observed in the present study [28]. Our results are supported by previous studies of metalstressed rice plants in which inoculation with Bacillus cereus and Bacillus subtilis remarkably increased shoot and root growth [45,46], which could be attributed to the phytohormone production and phosphate solubilization potential of inoculated rhizobacterial strains that help rice plants to acclimatize against the stressful environments [47]. Thus, it can be concluded that improvements in plant growth by Pb-resistant rhizobacterial strains in Pbcontamination soils could be due to phosphate solubilization, phytohormone production, siderophore production, and induced systemic resistance in metal-stressed plants [13,14,39].…”
Section: Discussionsupporting
confidence: 91%
“…B. cereus strains are also capable of mitigating plant stress caused by heavy metals, including arsenic, nickel, bo r, cadm, chromium, lead, copper, and zinc [60,[68][69][70][71]. Under cadmium stress conditions (pot experiment), B. cereus S6D1-105 was able to promote the growth of rice under hydroponic conditions.…”
Section: Bacillus Cereus In the Alleviation Of Abiotic Stressmentioning
confidence: 99%
“…Under cadmium stress conditions (pot experiment), B. cereus S6D1-105 was able to promote the growth of rice under hydroponic conditions. Cd-tolerant B. cereus had the ability to, for example, solubilize potassium and phosphate and produce siderophores, thereby increasing plant biomass, chlorophyll content, and antioxidant enzyme activities, including polyphenol oxidase, catalase, superoxide dismutase, and ascorbate peroxidase and reducing malondialdehyde in either rice leaves or roots [68]. Similar patterns were also obtained by other authors, e.g., Sahile et al [69] documented that B. cereus ALT1 reduces ABA and enhances SA contents in soybean plants under Cd stress conditions (growth chamber conditions).…”
Section: Bacillus Cereus In the Alleviation Of Abiotic Stressmentioning
confidence: 99%
“…Plants’ antioxidant systems can be stimulated to combat the oxidative injuries induced by salt stress. These responses include the removal of ROS by enzymes such as ascorbate peroxidase (APX), superoxide dismutase (SOD), and catalase (CAT) ( Zhu, Gong & Yin, 2019 ; Jabeen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%